Fight for Vilnus 19–21 April 1919 - Wojtaszak, Andrzej (City and War, 2021)
During the fights for the borders of the Commonwealth after World War I (until 1921), Vilnius was occupied by four armies: the German (Ober-Ost), Soviet, Lithuanian and Polish. The presented study concerns the battles for Vilnius in April 1919. As part of the socalled the Vilnius offensive, troops of the cavalry rally group (1st Cavalry Brigade), commanded by Lt. Col. Władysław Belina-Prażmowski and the 2nd Legion Infantry Division, commanded by General Edward Śmigły-Rydz, took the city. In the three-day fights in the city, the inhabitants themselves played an important role, especially the railwaymen and workers from the Society of St. Kazimierz. The actions taken by the Polish troops resulted from the general assumptions of the Vilnius operation, were based on the concept of a quick cavalry raid, surprise the enemy and the seizure of important city facilities (railway station, barracks, river bank of the Willia). After three days, thanks to the support of the 2nd Legions Infantry Division, the city was seized. The experience of the fights for Vilnius (200 000) was to be used in the further period of the Polish-Bolshevik war. The city itself was seized in October 1921 (as a result of the „putsch”) by the army commanded by General Lucjan Żeligowski, and from March 1922 it finally became part of the Second Polish Republic.